(untitled) (European Science Methodical Journal, 2026)
To successfully combine laser technology with nanomedicine, it is important to have a good insight into the optical properties of drug carriers. The paper will describe the Quantum Efficiency (QE) and Optical Absorption of two different types of nanomaterials: carbon-based Graphene Quantum Dots (GQDs) synthesized by hydrothermal, biogenic (green), and Laser Ablation in Liquids (LAL) synthesis, and metallic nanoparticles (AgNPs and AuNPs). The main goal was to establish the correlation between structural property - e.g. particle size, surface defects and functionalization - and the photonic performance of the material under laser irradiation. It was shown in the experiment that LAL-produced AuNPs are more monodispersed and reach a high Surface Plasmon Resonance (SPR) peak at 520 nm as compared to other methods, which are more suited to photothermal work. On the other hand, organic capping layers resulted in broader absorption profiles in biogenic AgNPs. GQDs exhibited a high intrinsic QE of 18.4 percent with regards to the carbon-based carriers. When loaded with the anticancer drug Doxorubicin (DOX), the QE considerably dropped to 9.2% which is due to a Fluorescence Resonance Energy Transfer (FRET) process, essentially acting as an optical signal-off detector in drug conjugation. In order to triangulate these experimental results, DFT calculations were done with the B3LYP functional. The theoretical models estimated a decrease in HOMO-LUMO gap to 2.98 eV (GQD-DOX complex) compared to 3.65 eV (bare GQD) which was consistent with experimental optical data with a variation of less than 6%. As the current paper confirms, the combination of advanced laser spectroscopy and theoretical modeling allows building a powerful framework of the design of smart, optically active drug delivery system.